2023
DOI: 10.7759/cureus.36070
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines' Role in the Pathogenesis and Their Targeting for the Prevention of Frozen Shoulder: A Narrative Review

Abstract: Frozen shoulder (FS) is a common name for shoulder movement limitation with different degrees of shoulder rigidity and pain. It is characterized by varying developmental courses, different levels of shoulder movement limitation, and background ambiguity due to the multiplicity of its causative factors. Systemic inflammatory cytokines monitoring and restraining is easy to apply, fast to conduct, and needs lower costs compared to invasive methods for frozen shoulder stage evaluation and early controlling of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
0
0
1
Order By: Relevance
“…The pathophysiology of adhesive capsulitis secondary to improper IM vaccination administration is not fully understood. Previous studies have found an increased expression of inflammatory mediators (interleukins, tumor necrosis factor-alpha {TNF-α}, tumor necrosis factor-beta {TNF-β}, and vascular endothelial growth factor {VEG-F}) in the joint capsule of patients with adhesive capsulitis [9]. It is postulated that improper injection of tetanus and diphtheria toxoids into the glenohumeral joint capsule leads to a significant inflammatory response within the joint, triggering adhesive capsulitis.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of adhesive capsulitis secondary to improper IM vaccination administration is not fully understood. Previous studies have found an increased expression of inflammatory mediators (interleukins, tumor necrosis factor-alpha {TNF-α}, tumor necrosis factor-beta {TNF-β}, and vascular endothelial growth factor {VEG-F}) in the joint capsule of patients with adhesive capsulitis [9]. It is postulated that improper injection of tetanus and diphtheria toxoids into the glenohumeral joint capsule leads to a significant inflammatory response within the joint, triggering adhesive capsulitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterised by varying developmental courses, different levels of shoulder movement limitation, and background ambiguity due to the multiplicity of its causative factors. 13 This study was conducted to evaluate the efficacy of different manual therapy interventions in improving pain and ROM. This study consists of six groups of manual therapy interventions, namely: 1.…”
Section: Discussionmentioning
confidence: 99%
“…Частота синдрома сдавления ротаторов плеча (ССРП), или субакромиального импинджментсиндрома, колеблется от 4,6 до 46,0% в зависимости от изучаемой популяции [3]. Адгезивный капсулит ПС поражает от 2 до 5% жителей Земли и наблюдается у 30% пациентов с сахарным диабетом (СД) 2-го типа 50 лет и старше [6]. Кальцифицирующий тендинит является причиной ХБОП в 7-17% случаев [7].…”
Section: хроническая боль в области плечевого сустава (хбоп) -клиниче...unclassified